PENDIDIKAN ISLAM MULTI, INTER, DAN TRANSDISIPLIN (TINJAUAN SEJARAH) - Ali Akbar; Mahyuddin Barni (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2022)
Islamic education has its uniqueness. The discussion about it can be multi, inter, transdisciplinary, and its history. This research showed: first finding, Islamic education is expected to be solution for social problems. Second, multidisciplinary Islamic education that involves other scientific perspectives to solve a problem that Muslim face in this era. Third, interdisciplinary education integrates the other knowledge groups through the learning process. Fourth, transdisciplinary Islamic education as a result of open dialogue with else disciplines. Fifth, the history of Islamic education basically starts from homes and mosques with a direct system until now with a classical and curriculum.Pendidikan Islam memiliki keunikan. Keluasan bahasannya dapat ditelaah secara multi, inter, transdisiplin, dan sejarah. Temuan penelitian ini adalah: pertama,  pendidikan Islam diharapkan menjadi solusi atas permasalahan sosial. Kedua, pendidikan Islam multidisipliner melibatkan perspektif ilmu lain untuk memecahkan suatu masalah. Ketiga, pendidikan interdisipliner mengintegrasikan rumpun ilmu lainnya melalui proses pembelajaran. Keempat, pendidikan Islam transdisipliner sebagai hasil dari dialog terbuka dengan  disiplin ilmu lainnya. Kelima, sejarah pendidikan Islam pada dasarnya berawal dari rumah dan masjid dengan sistem penyampaian secara langsung, berlangsung hingga saat ini dengan sistem kelas dibarengi dengan sistem kurikulumKEYWORDS: Islamic Education, Multi, Inter, Transdiscipline, Historical